Low Crude Protein Corn and Soybean Meal Diets with Amino Acid Supplementation for Broilers in the Starter Period. 2. Effects of Feeding 13% Crude Protein - McGill, E.; Kamyab, A.; Firman , J.D. (International Journal of Poultry Science, 2012)
Two experiments were conducted with the objective of testing the effects of feeding 13% CP diets with crystalline amino acid supplementation and various protein equivalents on the performance of broilers in the starter growth period. In each experiment, commercial broilers were fed a diet formulated to meet NRC requirements for the first seven days. The diet contained 23% CP and 3200 kcal/kg ME and also served as the Positive Control Diet (PC). On day 7, birds were sorted by weight into battery pens with 5 birds per pen. In the first experiment, six dietary treatments were utilized with eight replicates per treatment for a total of 48 pens. For the remaining dietary treatments, 13% CP diets were formulated and various levels of crystalline amino acids were added back to meet either digestible amino acid levels from a 22% CP diet from previous experiments from our lab at the University of Missouri (Guaiume, 2007) or digestible amino acid requirements set by Baker and coworkers (1993) using the ideal protein concept. One treatment using the University of Missouri values contained no glutamic acid and a low protein equivalent of 15.5% (MLPE), while others contained varying levels of glutamic acid to achieve a high protein equivalent of 20% (MHPE) or a mid-level protein equivalent of 18% (MMPE). Similarly, two treatments were developed using Baker et al. (1993) amino acid values and glutamic acid to achieve a 20% high protein equivalent (BHPE) or an 18% mid-level equivalent (BMPE). In Experiment 2, four dietary treatments with 12 replicates were utilized for a total of 48 pens. The same 23% CP diet used as the PC in Experiment 1 was utilized in Experiment 2. The remaining treatments in Experiment 2 consisted of 13% crude protein diets with crystalline amino acids added back to meet control levels and either no glutamic acid to yield a protein equivalent of 17.5% (PE-17.5), or glutamic acid added to meet an 18.75% (PE-18.75) or 20% (PE-20) protein equivalent. All diets were formulated on a digestible basis and were designed to be isocaloric. Birds received feed and water ad libitum. At the conclusion of each experiment, Body Weight Gain (BWG), Feed Intake (FI) and Feed:Gain (F:G) were measured. In Experiment 1, birds consuming the PC treatment achieved significantly greater (p<0.05) BWG than birds in any other treatment. A significant difference (p<0.05) in intake was seen between the BMPE treatment and all others. A significantly improved F:G (p<0.05) was observed in the PC treatment. Additionally, the BMPE treatment resulted in impaired F:G (p<0.05) when compared to the MMPE and MHPE treatments. In Experiment 2, birds receiving the PE-17.5 treatment gained significantly less weight (p<0.05) than those consuming other dietary treatments. There were no significant differences (p>0.05) in feed intake. Birds in the PC groups displayed significantly improved F:G over all other treatments (p<0.05).